Aspectos fisiológicos, bioquímicos, biofísicos e ultraestruturais associados à criopreservação em sementes de Coffea arabica L. - Souza, Ana Cristina de (2019)
Desiccation tolerance is the ability to recover metabolic activities after the partial removal of cellular water in seeds, allowing their survival. The long-term conservation, temperature in liquid nitrogen, is economically viable compared to the conservation of plants in the field. Research on desiccation tolerance and cryopreservation methods contribute to the understanding of the behavior of these seeds in relation to sensitivity, desiccation and cooling. In this context, studies were carried out with the objective of investigating the physiological, biochemical, biophysical and ultrastructural aspects of Coffea arabica L. seeds. In the first study, the objective was to investigate long-term storage methods of coffee seeds, performing physiological studies, biochemical and ultrastructural studies related to the effects of dehydration, precooling and reheating after exposure to liquid nitrogen. In the second study, the calorimetric properties of the crystalline cytoplasmic agents associated with cryopreservation were investigated. The physiological quality of Coffea arabica L. seeds is reduced as they lose water during drying. Reheating at a temperature of 25 ° C or a 40 ° C water bath of Coffea arabicaL. seeds after pre-cooling at a rate of 1 ° C min-1 to -40 ° C does not alter the physiological quality and the electrophoretic profile of the catalase and superoxide dismutase enzymes. The enzymes polyphenol oxidase and peroxidase present lower expression in electrophoresis gel in Coffea arabicaL. seeds reheated at 25 ° C. than in a water bath at 40 ° C, after pre-cooling at a rate of 1 ° C min-1 to -40 ° C. Damage to cell membranes has been found to be less drastic in seeds that are cryo-stored after drying. Seeds of Coffea arabicaL. dried in silica gel up to 20 or 17% (bu), pre-cooled in a biofreezer or directly immersed in liquid nitrogen, present high survival. In Coffea arabicaL. seeds with water contents, (43 and 35% bu) the melting enthalpy and the percentage of freezing water are higher than in seeds with water contents of 20, 17 or 12% bu. The melting point of frozen water in hydrated seeds occurs at temperatures below the melting temperature of pure water of 0 ° C. The formation of intracellular glasses in hydrated seeds was detected at temperatures of -18 and -22 ° C, seeds with 17 and 20% (bu) between -20 and -23 ° C and in cryo-stored seeds at -18 ° C.